Improving of 100Cr6 Steel Corrosion and Wear Properties in Simulated Sea Water Environment by Tungsten-Doped DLC Coating - Vicen, Martin; Kajánek, Daniel; Trško, Libor; Bokůvka, Otakar; Buchtík, Martin; Florková, Zuzana; Frkáň, Martin (MDPI, 2023)
A progressive type of tungsten-doped DLC coating was applied to a quenched and tempered 100Cr6 steel with the aim to improve the wear and corrosion properties in simulated seawater conditions and to compare the performance to conventional DLC coating. Tungsten doping caused a shift of the corrosion potential (Ecorr) to a lower negative value of 172 mV, while the conventional DLC exhibited an Ecorr of 477 mV. In dry conditions, the W-DLC coefficient of friction is slightly higher than that of the conventional DLC (0.187 for the W-DLC vs. 0.137 for the DLC), but in cases of a saltwater environment, this difference becomes almost negligible (0.105 for the W-DLC vs. 0.076 for the DLC). The conventional DLC coating also started to show marks of deterioration when exposed to a combination of wear in a corrosive environment, while the W-DLC layer still maintained its integrity.

A progressive type of tungsten-doped DLC coating was applied to a quenched and tempered 100Cr6 steel with the aim to improve the wear and corrosion properties in simulated seawater conditions and to compare the performance to conventional DLC coating. Tungsten doping caused a shift of the corrosion potential (Ecorr) to a lower negative value of 172 mV, while the conventional DLC exhibited an Ecorr of 477 mV. In dry conditions, the W-DLC coefficient of friction is slightly higher than that of the conventional DLC (0.187 for the W-DLC vs. 0.137 for the DLC), but in cases of a saltwater environment, this difference becomes almost negligible (0.105 for the W-DLC vs. 0.076 for the DLC). The conventional DLC coating also started to show marks of deterioration when exposed to a combination of wear in a corrosive environment, while the W-DLC layer still maintained its integrity.
Improving of 100Cr6 Steel Corrosion and Wear Properties in Simulated Sea Water Environment by Tungsten-Doped DLC Coating
Keywords: DLC coating; W-DLC coating; wear; tribology; corrosion resistance; DLC coating; W-DLC coating; wear; tribology; corrosion resistance